Dini tutum ve davranışların oluşumunda mükafat ve cezanın etkisi - Hümbetova, İrade (My University, 2011)
Foreign Direct Investments ABSTRACT Foreign direct investment means; capital, employment, technology and exportation possibilities for developing countries. In this context, foreign direct investment’s importance for developing countries is an undeniable fact. In this study, it has been trying to find out foreign direct investment’s affects on Turkey after 2001. In the first section of this study, international capital movements and especially foreign direct investments and their characteristics are examined. In the second section of this study foreign direct investment’s positive and negative aspects are revealed. In the last section of this study foreign direct investment’s process and after 2001 are examined.
Keywords: Din Sosyolojisi